Academic Capital and the Career Orientations of High School Students. Issue 2 (1st February 2018) - Zaichenko, N.A.; Vinokurov, M.V.
Abstract : In this study, we explore how career orientations of Russian high schoolers are related to the quality of their academic capital. We introduce and validate the concept of the academic capital of high school students. We describe why we chose Schein's Career Orientations Inventory as a screening instrument, which allows us to determine whether the individual is aware of their vector of future career advancement, and we propose how the instrument can be modified to be used among the cohort of high school students that form the subject of our study. During the course of the study, we tested three hypotheses of the interrelationship between the academic capital of high school students and their career orientations.